Impact of a comprehensive tobacco control policy package on acute myocardial infarction and stroke hospital admissions in Beijing, China: interrupted time series study. Issue 4 (15th July 2020) - Zheng, Yunting; Wu, Yiqun; Wang, Mengying; Wang, Zijing; Wang, Siyue; Wang, Jiating; Wu, Junhui; Wu, Tao; Chang, Chun; Hu, Yonghua
Abstract : Objective: To evaluate a comprehensive tobacco control policy package on hospital admissions for acute myocardial infarction (AMI) and stroke in a global city. Design: Interrupted time series study. Setting: Beijing, China. Population: 31 707 AMI and 128 116 stroke hospital admissions recorded by the Beijing Medical Claim Data for Employees in 17.7 million residents from January 2013 to June 2017. Intervention: The policy package including all components of MPOWER has been implemented since June 2015. Main outcome measures: The immediate change of AMI and stroke hospital admissions and the annual change in the secular trend. Results: There was a secular increase trend for the crude hospital admission rates of AMI and stroke during the observational period. After implementation of the policy, immediate reductions were observed in the hospital admissions for both AMI (−5.4%, 95% CI −10.0% to −0.5%) and stroke (−5.6%, 95% CI −7.8% to −3.3%). In addition, the secular increase trend for stroke was slowed down by −15.3% (95% CI −16.7% to −13.9%) annually. Compared with the hypothetical scenario where the policy had not taken place, an estimated 18 137 (26.7%) stroke hospital admissions had been averted during the 25 months of postpolicy period. Conclusions: The results indicated significant health benefits on cardiovascular morbidity after the Beijing tobacco control policy package, which highlighted the importance for a comprehensive tobacco control policy at the national level in China. Similar tobacco control policy which consists of all components of MPOWER is urgently needed in other areas, especially in settings with high tobacco consumption, to achieve greater public health gains.